1983
DOI: 10.2307/3897952
|View full text |Cite
|
Sign up to set email alerts
|

Diets of Bison and Cattle on a Seeded Range in Southern Utah

Abstract: Diets of bison ( Bison bison) mnd cattle (Bos taurus) were evaluated on a southern Utah range seeded to crested wheatgrass (Agropyron desertorum) and alfalfa (Medicago sativa). Bison feces comprised 96% grasses and sedges, 4% forbs, and 1% shrubs. Cattle feces comprised 88% grasses and sedges, 4% forbs, and 8% shrubs. Diets were 91% similar, indicating a high potential for competition between bison and cattle.The Henry Mountains of southern Utah have been used as summer range by cattle (Bos taurus) since the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 3 publications
0
26
0
Order By: Relevance
“…Apart from bison, cattle are the only other large grazers in the region. The HM are host to a healthy herd of mule deer (Odocoileus hemionus), but their preference for forbs would suggest negligible levels of competition with the grazers (van Vuren and Bray, 1983). A small (∼20) herd of elk (Cervus canadensis) is also present on the HM, though the Utah Division of Wildlife Resources actively manages against elk in an attempt to eradicate the herd.…”
Section: Study Areamentioning
confidence: 99%
“…Apart from bison, cattle are the only other large grazers in the region. The HM are host to a healthy herd of mule deer (Odocoileus hemionus), but their preference for forbs would suggest negligible levels of competition with the grazers (van Vuren and Bray, 1983). A small (∼20) herd of elk (Cervus canadensis) is also present on the HM, though the Utah Division of Wildlife Resources actively manages against elk in an attempt to eradicate the herd.…”
Section: Study Areamentioning
confidence: 99%
“…Numerous studies have shown that bison preferentially graze grasses over other plants (Meagher 1973 ;Peden et al 1974 ;Schwartz and Ellis 1981 ;Van Vuren and Bray 1983 ;Plumb and Dodd 1993 ;Steuter et al 1995), creating distinct grazed patches within the landscape and altering competitive relationships among grazed and ungrazed plant species Knapp 1993, 1994 ;Catchpole 1996). Bison and other ungulate herbivores also significantly alter nutrient cycling through grazing and other activities (Floate 1981 ;Ruess 1987 ;McNaughton et al 1988 ;Frank et al 1994 ;Frank and Evans 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Competition, however, is difficult to manage, and so it is important to quantify bison habitat use before implementing management actions aimed at addressing perceived conflicts with cattle habitat needs. Early work in the HM discovered that bison and cattle have 91% dietary similarity (van Vuren & Bray, 1983), indicating a high potential for competition and leading to a local perception that bison are strong competitors with cattle for grazing resources. Dietary overlap alone might not, however, be an indicator of competition if habitat use by bison and cattle is differentiated in time and space.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Apart from bison, cattle are the only other large grazers in the region. Mule deer (Odocoileus hemionus) are present on the HM, but their preference for forbs suggests negligible levels of competition with the grazers (van Vuren & Bray, 1983). A small herd (~20 animals) of elk (Cervus canadensis) is also present, though the Utah Division of Wildlife Resources actively manages against elk, using sport hunting in an attempt to eradicate the herd to prevent competition with the highly prized mule deer.…”
Section: Study Areamentioning
confidence: 99%